2016
DOI: 10.26417/ejser.v7i1.p37-47
|View full text |Cite
|
Sign up to set email alerts
|

Small Steps, Giant Leaps: Project-based Learning in a Conservative Educational System. Greek Students’ Views

Abstract: The present questionnaire-based study examines 170 Greek upper secondary public and private education students' perceptions about the factors that facilitate or undermine project-based learning within the framework of the highly conservative Greek educational system, about the cognitive, affective and social skills they developed during the carrying-out of project procedures, and about the levels of satisfaction they experienced during their cooperation with their supervising teachers. According to the results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The body In recent years, collaborative learning has been the subject of intense academic debate due to the increasing importance of working in teams to solve increasingly challenging problems in modern life and work (Du et al, 2022). In this context, the idea of collaborative work as a method of promoting social and relational skills in the classroom, such as sociability, cooperativeness, responsibility, empathy, tolerance, as well as feelings of self-esteem, usefulness and acceptance, began to develop in the 1970s (Bores -García et al, 2021;Kaldi et al, 2009;Koutrouba & Alexaki, 2016;Mpotsoglou et al, 2007;Ferguson -Patrick, 2022;Tzika et al, 2015). Scientific literature has shown that a child learns to function socially in a school (Santamaría -Villar et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The body In recent years, collaborative learning has been the subject of intense academic debate due to the increasing importance of working in teams to solve increasingly challenging problems in modern life and work (Du et al, 2022). In this context, the idea of collaborative work as a method of promoting social and relational skills in the classroom, such as sociability, cooperativeness, responsibility, empathy, tolerance, as well as feelings of self-esteem, usefulness and acceptance, began to develop in the 1970s (Bores -García et al, 2021;Kaldi et al, 2009;Koutrouba & Alexaki, 2016;Mpotsoglou et al, 2007;Ferguson -Patrick, 2022;Tzika et al, 2015). Scientific literature has shown that a child learns to function socially in a school (Santamaría -Villar et al, 2021).…”
Section: Introductionmentioning
confidence: 99%